(3fHP COHjI aj GdeLhfs - (3eLghds
(3ChdgG (B:s
(3aUd ef GdeLhf(B: (3dHYVge(B: (3bGdhG JQcJ GdTYQ bdJ VQhQI HGH GdOhGYj hGdHhGYK oeZdb s
(3BNQgG (B:s
(3aSbWJ fbWI ef GdTeYI Ydi hLg GdbGVj aaJM Yjfjg (B((3h(B) (3hLO eMHhHg aCfTO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGef YTQs
(3GdNW bdjd GdfbWs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B125 s
Keywords: (3GdCOHs